(untitled) (Al-Qamar, 2025)
Khānqahī system has always facilitated the suffering humanity in terms of not only providing them with the resources to meet the basic necessities of life but also showing them the right path to lead their life according to the teachings of Sharī̒ah and Tarīqah. This research article is a comparative study between the management of "Khānqāhs" presently administered by the Department of Auqaāf and those under the supervision of the successors (Sajjāda Nasheens) of Sufis and their outcomes for the character building of their followers. The research has adopted mixed research method to pinpoint the significant difference in the management of these Khanqahs and their resultant outcomes for the welfare of the general visitors. The data has been collected through questionnaires for visitors and the managers of these Khānqāhs both from public sector and the successors (Sajjāda Nasheens) of Sufis. There has been found significant difference between the opinion of the visitors of Khanqahs under the supervision of the government and those which are supervised by the successors (Sajjāda Nasheens). To conclude, this finding provides a strong common ground for a collective effort to revive Khānqāhī system to upgrade the moral values of people of the contemporary society by revamping character-building programs according to the present-day needs.